Estrada i liryka. Szlagier w poezji międzywojennej - Łuszczykiewicz, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
In the essay the author enquires into the references to popular song in the lyric poetry ofthe first decades of 20th century, treating the birth of the popular music as the beginningof perceiving a hit single as the integral piece meant to be shown to the public. The researcherasks about acceptability and, eventually, the consequences of the artistic flirt ofhighbrow literature with egalitarian word-music tradition. Moreover, the author showsvarious scenario of treating hit song impulses, beginning with total ignorance shown byYoung Poland artists (Jan Kasprowicz, Bolesław Leśmian, Leopold Staff), through theseparation of serious creativity from stage gainful employment, as in the case ofSkamander members fearing being given the label of cabaret entertainers (Julian Tuwim,Antoni Słonimski or Marian Hemar), until the liquidation of barriers between seriousand jocular muse domains, as in Konstanty Ildefons Gałczynski’s lyric poetry. In thisarticle, there are dozens of allusion, quotations, paraphrases, all invoking not only themost popular hit singles of the Interbellum, but also songs which were less known andtherefore nowadays seem to be more difficult to identify. The list of the poets is extendedby such personages as Bruno Jasieński, Maria Pawlikowska, and finally Czesław Miłosz.